Allelopathic Effect of Echinochloa colona L. and Cyperus iria L. Weed Extracts on the Seed Germination and Seedling Growth of Rice and Soyabean - Neha Chopra; Geeta Tewari; Lalit M. Tewari; Brij Upreti; Naveen Pandey (Advances in Agriculture)
The present study was undertaken to assess the allelopathic effect of Echinochloa colona L. and Cyperus iria L. in relation to the germination and primary growth of Oryza sativa L. (rice) and Glycine max L. (soyabean). Effects of dichloromethane (DCM) and double distilled water soluble (DDW) fractions of E. colona L. and C. iria L. root and aerial part extracts reduced germination and suppressed early seedling growth of rice and soyabean. With increase in extract concentration from 1 to 100 mg/mL, a gradual decrease in seed germination and seedling length occurred. The highest growth of G. max seedling was recorded in DDW fraction of E. colona aerial part extract at 1 mg/mL concentration with 94% germination and the lowest length was found in DCM fraction of C. iria root extract at 100 mg/mL concentration with 65% germination. In O. sativa, the highest length was noted at 1 mg/mL concentration in DDW fraction of E. colona aerial part extract with 82% germination and the lowest length was found in DCM fraction of C. iria and E. colona root extracts with germination 57% and 62%, respectively, at 100 mg/mL concentration. The results suggested that these weeds had good allelopathic potential which reduces germination and plant growth.